Effectiveness of electrical stimulation in idiopathic Parkinson’s disease - NKC, Ebrahim; AP, Krishna; Ovallath, Sujith (International Journal of Research in Medical Sciences, 2017)
Background: Parkinson’s disease is one of the most disabling chronic neurologic diseases and leads to a significant loss of quality of life. Electrical stimulation activate nerves innervating extremities affected by paralysis resulting from Spinal Cord Injury (SCI), head injury, stroke and hence is primarily used to restore function in people with disabilities. Methods: The study was performed after the institutional ethical clearance and informed consent from all the participants. The parameters assessed were time taken to complete 20 M walk with turn round, distance covered in the first 3 minutes of walking, gait dynamics like stride length, step length and cadence and number of falls with the help of video tape recorder, stop watch and measuring tape. Results: We observed a non-significant reduction (P = 0.471) of UPDRS, mean score of PDQ-39 was declined non-significantly (P = 0.36), time taken to complete 20 meters walk with turn was declined significantly (P = 0.017), The distances walked in 3 minutes by the patients were increased significantly (P = 0.000), number of steps during 20 meter walk was recorded and was found to be declined significantly (P = 0.088), stride length of the patients were increased significantly (P = 0.000), step length of the patients was increased significantly (P = 0.000), average number of falls reduced significantly (P = 0.00) during the stimulation period from week 0 to week 8. Conclusion: This study demonstrated the superior efficacy of electrical stimulation over best medical management in patients with advanced Parkinson’s disease.